Desenvolvimento e caracterização tribológica de materiais resistentes ao desgaste abrasivo para industria mineradora de cassiterita - Máscia, Roberto (2002)
During the cassiterite ore processing, a mixture containing mainly silicon oxide, cassiterite, iron oxides and water is guided through different crushing mills and pumps in order to reduce and separate it. These operations lead to large maintenance costs due to abrasive and erosive wear. To reduce wear in this field, the high chromium white cast irons are widely used in the crushing mills and pump parts. Tool steels, such those containing up to 1 wt. percent of carbon and 12 wt. percent of chromium have been used to protect the internal surface of bar mills. This work presents a set of different analysis, which were carried out to find out, first of all, the underlying wear mechanisms and so an appropriate wear laboratory test. The wear behaviour of hammer crushing mills was analyzed using an equipment based on the two body abrasion. High chromium white cast irons containing 15 wt. percent of chromium, 2 wt. percent of molybdenum and up to 1,5 wt. percent of niobium with different microstructures were produced, as an attempt to reduce the abrasive wear. The abrasive wear rate was measured using Si02 as abrasive and compared with the wear rate of commonly used white cast iron for hammer mills. It has been found the abrasive wear rate increased significantly with decreasing austenitizing temperature. The tempering temperatures also may considerably change the wear behaviour. A significant reduction on the wear rate was observed on the white cast irons with a niobium percentage between 0,5 and 1,0 percent. To simulate the wear behaviour of bar crushing mills, an equipment based on the lapping principle was used. Sand with an average grain diameter of 150 pm was selected as abrasive. The results showed that using a carbon steel as a counter-body and a nominal test pressure of 0,40 MPa, the abrasive particles are embedded in the carbon steel leading to a two body configuration. On the other hand, the use of a hard counter-body made of a high chromium white cast iron may lead to much less embedding and the three-body abrasive wear configuration predominates. Although, this situation can be modified during the test as consequence of the abrasive particle fragmentation. An increase of the wear test load may accelerate this change. Using the parameters which lead to a three-body abrasive wear no significant change could be observed between the studied steels. This suggests that the chromium content may be strongly reduced, and consequently the maintenance price of this kind of mills, without a marked reduction on the wear resistance. Finally to simulate the wear behaviour of pump parts a slurry pot were designed and constructed. A suspension of sand (5 % weight) was used and the impingement velocity was fixed at about 8 m/s. Different quenched and tempered high chromium white cast irons were tested. The wear mechanisms were analysed. The wear tests showed a positive influence of the M7C3 carbides and the addition of up to 1 weight percent of molybdenum considerably increased the wear resistance. Additionally, an analyses of the initial reduction of the wear rate was found to be mainly related to a reduction of the abrasive sharp cutting edges during the test.